Ceilings of the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
The ceilings of the rangamandapa (open type of pillared hall) are intricately carved, presenting a variety of ceiling types and motifs. One of the rectangular ceilings depicts a full-blown lotus, with the figure of a divine couple at the centre. The male deity is shown seated, holding his attributes and embracing his consort, who is shown seated in his lap. The central flower is surrounded by four small flowers, each also depicting a divine figure at the centre.